2012
DOI: 10.1016/j.urology.2011.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Mannitol Use Does Not Improve Long-term Renal Function Outcomes After Minimally Invasive Partial Nephrectomy

Abstract: OBJECTIVE To evaluate intravenous mannitol during minimally invasive partial nephrectomy (PN) by comparing the renal function outcomes of the patients who received it versus those who did not. METHODS Of 285 consecutive elective minimally invasive PN cases from February 2005 to July 2010, 164 patients (58%) were treated with mannitol. We compared the renal function recovery using a multivariate generalized estimating equation linear model of estimated glomerular filtration rate (eGFR) controlling for nephrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 20 publications
1
29
0
1
Order By: Relevance
“…They, too, did not find any evidence that mannitol was significantly associated with improved renal function recovery over time. 3 Multivariate analysis in the present study supports the notion that ischemia time is an independent predictor of renal function after PN. 25 A recent study suggested that the amount of preserved parenchyma and its baseline functionality could be the primary determinants of ultimate renal function after PN, although type and duration of ischemia remain the most important factors.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…They, too, did not find any evidence that mannitol was significantly associated with improved renal function recovery over time. 3 Multivariate analysis in the present study supports the notion that ischemia time is an independent predictor of renal function after PN. 25 A recent study suggested that the amount of preserved parenchyma and its baseline functionality could be the primary determinants of ultimate renal function after PN, although type and duration of ischemia remain the most important factors.…”
Section: Discussionsupporting
confidence: 86%
“…Mannitol has traditionally been administered before PN to reduce ischemic renal damage as an intravascular volume expander with a purported function of free radical scavenging, as well as being an osmotic diuretic. [1][2][3] However, we do not have any high-level clinical evidence of its effectiveness. In fact, a potential deleterious effect of mannitol related to increased tubular oxygen demand has been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many surgeons prefer to use mannitol and/or furosemide during PN, which may optimize reperfusion and increase diuresis [57]. However, several recent studies do not support the use of mannitol during PN [58], even in solitary kidneys [59]. Cooling with ice slush is the classical strategy for cold ischemia during OPN [56], but has also been applied in minimally invasive approaches [60,61].…”
Section: Evidence Synthesismentioning
confidence: 99%
“…There are no randomised trials supporting its use during NSS, and furthermore, there have been studies demonstrating no benefit in renal function within six months of NSS with mannitol use. 33 The mean peri-operative blood loss is similar in both groups, and no significant difference was seen. Similar results are seen in current case series.…”
Section: Discussionmentioning
confidence: 78%